COMPARISON OF FIELD PERFORMANCE AND FRUIT QUALITY AMONG NEWLY RELEASED ITALIAN JUNE-BEARING STRAWBERRY CULTIVARS - Milivojević, Jasminka; Radivojević, Dragan; Milosavljević, Dragica; Maksimović, Vuk; Dragišić Maksimović, Jelena (Journal of Agricultural Sciences (Belgrade), 2023)
This study illustrates the differences in phenology, vegetative growth, productivity and fruit quality of newly released June-bearing strawberry cultivars (‘Quicky’, ‘Sandra’, ‘Lofty’, ‘Mila’ and ‘Aprica’) aiming to recognize their potential for wider cultivation. A field study was carried out in a strawberry plantation situated in municipality of Šid (Serbia), during the period of 2021 to 2022. The orchard was planted in July 2020 in double rows on beds covered with black polyethylene foil. Cultivars were evaluated for their flowering and ripening time, yield components, plant growth, as well as for biometrical fruit traits (fruit weight, index of fruit shape) and nutritional value (content of soluble solids - SS, total acids - TA, vitamin C, total anthocyanins –TACY, total phenolics - TPC and total antioxidant capacity - TAC). The results showed that cv. ‘Quicky’ started to ripen earliest, while cv. ‘Aprica’ was the latest in both experimental years. The number of branch crowns per plant was significantly higher in cvs. ‘Sandra’ and ‘Lofty’, whereby cv. ‘Sandra’ had also the highest number of leaves per rosette (41.5) in comparison with the other tested cultivars. Cv. ‘Aprica’ was superior in terms of productivity (1061 g/plant and 4.67 kg/m2) accompanied by the largest fruit weight (29.9 g) and index of fruit shape (1.15). Contrary to this, the lowest yield potential was found in cv. ‘Mila’ (608 g/plant and 2.68 kg/m2). Cvs. ‘Lofty’ and ‘Sandra’ ranked the highest in terms of SSC and they are also characterized by a considerably high level of TPC (1.29 mg GAE eq g-1 FW) and TACY (24.4 mg pg-3-g eq100 g-1 FW ), respectively.
Keywords: strawberry; cultivar; plant growth; ripening time; productivity; fruit quality